Free and Open Source Software in Costa Rican Local Governments - Mata, Francisco (2014)
This paper presents and discusses the results from an electronic survey on the use of free and open source software (FOSS) by local governments in Costa Rica. Barriers preventing the use of this type of software are also identified. Comparison of the results from this survey with those obtained from a previous one, conducted under the same project, shows that Costa Rican local governments are increasingly using FOSS. Cost advantages provided by FOSS might be the main reason for this trend. However, other factors need to be considered for justifying the use of FOSS. These factors need to be articulated into organizational strategies —issue in which Costa Rican local governments are falling behind.